2007
DOI: 10.1007/s11433-007-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

The research on the quantum tunneling characteristics and the radiation spectrum of the stationary axisymmetric black hole

Abstract: At the event horizon and the cosmological horizon of the stationary axisymmetricKerr-Newman black hole in the de Sitter space-time background, the tunneling rate of the charged particles is relevant with Bekenstein-Hawking entropy and the real radiation spectrum is not strictly pure thermal, but consistent with the underlying unitary theory in quantum mechanics. This is a feasible interpretation for the paradox of the black hole information loss. Taking the self-gravitation action, energy conservation, angular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…black hole, Fock representation, mass spectrum, quantum area spectrum, wave function of horizon area After Bekenstein's [1] and Hawking's [2] initial work, the thermodynamics and the statistic mechanics of black holes have been one of the important research areas. Especially in recent years, many authors have already obtained some interesting results on the thermal radiation and the entropy of black holes [3][4][5][6][7][8][9][10][11] . Many conclusions with various different methods revealed that the black hole's entropy is proportional to the horizon area.…”
mentioning
confidence: 99%
“…black hole, Fock representation, mass spectrum, quantum area spectrum, wave function of horizon area After Bekenstein's [1] and Hawking's [2] initial work, the thermodynamics and the statistic mechanics of black holes have been one of the important research areas. Especially in recent years, many authors have already obtained some interesting results on the thermal radiation and the entropy of black holes [3][4][5][6][7][8][9][10][11] . Many conclusions with various different methods revealed that the black hole's entropy is proportional to the horizon area.…”
mentioning
confidence: 99%
“…Via the point of view, people have put forward several methods, such as anomalies theory, to research on the Hawking radiation [3][4][5][6]. On the other hand, the Hawking radiation could be viewed as the realized particles radiation which becomes from virtual particles inside black holes across the horizon, and Parikh and Wilczek et al have brought forward the semi-classical approximation to research on the tunneling radiation via the point of view [7][8][9][10][11][12][13][14][15]. In the semi-classical approximation method, the WKB approximation is used, so that the tunneling rate ∝ exp(−2 Im S) is applied (S is the first term from the expanding classical action via ), and then, considering the relation between tunneling rate and Hawking temperature ∝ exp(−ω/T ), the Hawking temperature of the horizon can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…This supported the information conservation in Hawking radiation [25,26] . After this, in Parikh framework the primary result of Parikh was generalized to much static and stable spacetime [27][28][29][30][31][32][33][34][35][36][37][38][39][40] . Energy spectrum of any black hole radiation particles is e ,…”
Section: Introductionmentioning
confidence: 99%